2022
DOI: 10.1155/2022/1571801
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Dysfunction Impact on Life Quality in a Cohort of Russian Patients with Parkinson’s Disease I-III H&Y Stage

Abstract: Background. There are still no clearly proven methods to slow down or stop the progression of Parkinson’s disease (PD). Thus, improving the quality of life (QoL) of patients with PD becomes of primary importance. Autonomic dysfunction and its symptoms are known to worsen the quality of life in PD, but the degree of this influence is underinvestigated. Particularly, impacts of the separate significant gastrointestinal symptoms, such as dyspepsia, constipation, and abdominal pain, in PD should be more precisely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…reflux disease ≈ 9.6%-37% 17,18 Gastroparesis ≈ 25%-45% 15 Drooling (sialorrhoea) ≈ 10%-84% 13 Dyspepsia ≈ 20.8%-70.7% 14,24 • Helicobacter pylori infection ≈ 25%-58% are sometimes broadly termed by patients as 'indigestion' . These symptoms in PD may be due to a variety of upper GI problems, including dyspepsia, gastroparesis, small intestinal bacterial overgrowth (SIBO), and GI dopaminergic side effects of PD medications, as discussed below.…”
Section: Gastrooesophagealmentioning
confidence: 99%
See 1 more Smart Citation
“…reflux disease ≈ 9.6%-37% 17,18 Gastroparesis ≈ 25%-45% 15 Drooling (sialorrhoea) ≈ 10%-84% 13 Dyspepsia ≈ 20.8%-70.7% 14,24 • Helicobacter pylori infection ≈ 25%-58% are sometimes broadly termed by patients as 'indigestion' . These symptoms in PD may be due to a variety of upper GI problems, including dyspepsia, gastroparesis, small intestinal bacterial overgrowth (SIBO), and GI dopaminergic side effects of PD medications, as discussed below.…”
Section: Gastrooesophagealmentioning
confidence: 99%
“…9 The entire GI tract is affected in PD 7,10 and leads to a wide variety of issues, including oropharyngeal and upper-mid gut (stomach and small bowel) and lower gut (large bowel) problems (Figure 1). 1,[11][12][13][14][15][16][17][18] Oropharyngeal problems, such as sialorrhea and dysphagia, are prevalent in advanced PD and were recently reviewed elsewhere. 10,19 Gastric and bowel dysfunction are prevalent in early and later stages of PD, and manifest as heterogeneous upper and lower GI symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…For many patients with severe PD, the burden of GI symptoms has a greater impact on quality of life than even motor symptoms. 3 Like with other disorders of gut-brain interaction, the relationship between GI symptoms and mental health in PD is bidirectional: A recent study found that in PD both anxiety and depression were predicted by the degree of GI symptom burden, and inversely, worse anxiety and depression significantly predicted the development of poorer GI symptoms. 4 Over the last decades, significant attention has been paid to GI symptoms manifesting not only after a PD diagnosis, but in fact, occurring as many as 20 years prior.…”
mentioning
confidence: 99%